(untitled) (Journal of the College of Basic Education, 2022)
The cellulose-degrading fruiting slithering bacteria were isolated from clay soil samples fertilized with organic fertilizers spread in different places in the city of Baghdad, using palm fronds as a raw material for catching fruiting bodies and preparing a local culture medium from the cellulosic residue of palm fronds to isolate the vegetative clump. 25 soil samples based on the phenotypic characterization of the fruiting bodies and the vegetative clump.